Urinary incontinence in hospital in-patients: a nursing perspective - Cheater, Francine M. (1990)
Urinary incontinence is a common health problem with not only physical, but also far-reaching psychological and social implications for the sufferer, her family and carers. Assisting patients with meeting their eliminatory needs is a fundamental part of nursing care. Incontinence is encountered in almost every sphere of clinical practice and is a problem with which nurses are often directly concerned. Nurses, in association with other members of the health care team, have considerable potential to help patients regain continence, or when this is not possible, to ensure that the individuals concerned, and their relatives or carers, can cope effectively with the problem, both physically and psychologically. This is an area of nursing care, however, which to date has attracted little research.